Aile Danışmanlık Merkezine başvuran danışanların EYSENCK Kişilik Kuramına göre kişilik özelliklerinin incelenmesi - Çetinkaya, Kerime (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Bu araştırmanın amacı Aile Danışmanlık Merkezine başvuran danışanların Eysenck Kişilik Kuramına göre kişilik özelliklerinin incelenmesidir. Araştırmada nicel araştırma yöntemlerinden tarama modeli uygulanmıştır. Araştırmanın çalışma grubunu 2020-2021 yılında İstanbul ili Avrupa yakasında bulunan özel bir aile danışmanlık merkezine başvuran ve çalışmaya katılımı gönüllülük esası ile kabul eden 18 yaş üstü 161 kadın (%68,8) ve 73 erkek (%31,2) olmak üzere toplam 234 kişi oluşturmaktadır. Veri toplama araçları olarak araştırmacı tarafından hazırlanan "kişisel bilgi formu" ile "Eysenck Kişilik Anketi- Gözden Geçirilmiş Kısa Formu" (EKA-GGK) kullanılmıştır. Araştırma sorularının analizleri yapılmadan önce, ölçeklerden elde edilen verilerin normalliği Kolmogrov-Smirnov ve Shapiro-Wilk testlerine bakılarak sınanmıştır. Bu testlerde puanlar normal dağılım göstermediği için analizlerde parametrik olmayan testlerden, iki bağımsız grup kıyaslamasında Mann Whitney U testi, üç veya üçten fazla bağımsız grup kıyaslamasında Kruskal Wallis testi kullanılmıştır. Ayrıca Eysenck Kişilik Envanterinin alt boyutlarından Nörotisizm, Dışa dönüklük, Psikotisizm ve Yalan alt ölçek puanları arasındaki ilişkilerin belirlenebilmesi için Spearman korelasyon analizi yapılmıştır. Araştırma sonucunda Eysenck kişilik anketinin alt testlerinden cinsiyete göre nörotisizm ve psikotisizm özellikleri arasında anlamlı farklılıklar görülmekte, Yaş değişkenine göre ise nörotisizm ve yalan puanları arasında anlamlı farklılık görülmektedir. Medeni durumlarına göre dışadönüklük, nörotisizm ve psikotisizm arasında anlamlı bir fark görülmemekte iken Çocuk sahibi olma durumuna göre nörotisizm ve yalan arasında anlamlı fark görülmektedir. Çocuk sayılarına göre nörotisizm, dışadönüklük ve psikotisizm arasında anlamlı farklılık görülmemekte, eğitim durumlarına göre sadece dışa dönüklük özelliğinde fark görülmekte, eğitim kademesi arttıkça dışadönüklük puanında artış görülmektedir. Sosyo ekonomik düzeyde nörotisizm ve psikotisizm özelliklerinde anlamlı farklılık görülmektedir. Çalışma durumuna göre çalışanların nörotisizmi düşük görülmektedir. Aile danışmanlık merkezine daha önce başvurma durumlarına ve ikamet yerlerine göre ise dışa dönüklük, nörotisizm, psikotisizm ve yalan arasında anlamlı fark görülmemektedir. Araştırma bulguları ile ilgili alanyazın doğrultusunda tartışılmış ve ilerleyen dönemde yapılacak olan çalışmalara yönelik önermeler sunulmuştur.

The aim of this research is to examine the personalities of individuals who apply to family counselling center on the basis of Eysenck Personality theory. In the study, survey model which is one of the quantitative research method has been used. In the research, scanning model, which in one of the quantitave research methods, was applied. The study group consists of the research was 234 people, 161 women (68.8%) and 73 men (31.2%) over the age of 18, who applyed to a private Family Counseling Center ın the European side of Istanbul in 2020-2021 and agreed to participate in the study on a voluntary basis. The "personal information form" that prepared by the researcher regarding to demographic variables and H.J Ëysenck "Personality Questionnaire-Revised Short Form"(EKA-GGK) were used as data collection tools. The normalization of obtained data from scales were tested by the Kolmogrov- Smirnov and Shapiro-Wilk tests before analyzing the research questions. The scores do not show a normal distribution. Therefore, non-parametric tests were used in the analyzes of the research.Thus, the Mann Whitney U test was used in the comparison of two independent groups that did not have a normal distribution, ant the Kruskal Wallis test was used in the comparison of three or more independent groups. Finally, Neuroticism, a sub-dimension of the Eysenck Personality Invertory. Spearman correlation analysis was performed to determine the relationships between extraversion, As a result of the research, there are significant difference between neuroticism and psychoticism characteristic according to gender, one of the subsets of the Eysenck Personality Questionnaire. According to age variable, the significant difference can be observed between neuroticism and lie scores. While there is no significant difference between extraversion, neuroticism and psychoticism according to marital status, there is a significant difference between neuroticism and lying according to having children. There is no significant difference between neuroticism, extraversion and psychoticism regarding to the number of children. There is only a difference in extraversion regarding to educational status. When the education level increases, the extraversion score increases. There is a significant difference in the characteristics of neuroticism and psychoticism at the socio-economic level. The neuroticism of the employees is low regarding to the working status. There is no significant difference between extroversion, neuroticism, psychoticism and lying according to their previous application to the family counseling center and their place of residence. The research findings were discussed in line with the literature and suggestions for future studies were presented.
Studying the personality charactaristics of indiviuals who apply to the Family Counselling Center on the basis of EYSENCK Personality Theory
Keywords: Aile danışmanlığı; Kişilik; Dışa dönüklük; Nörotisizm; Psikotisizm; Yalan; Family counselling; Personality; Extroversion; Neuroticism; Psychoticism; Lying